2012
DOI: 10.1007/s10021-012-9619-y
|View full text |Cite
|
Sign up to set email alerts
|

Wind and Water Dispersal of Wetland Plants Across Fragmented Landscapes

Abstract: Biodiversity in wetlands is threatened by habitat loss and fragmentation, of which agricultural activities often are a cause. Dispersal of plant seeds via wind and ditches (water) may contribute to connecting remnant wetland plant populations in modern agricultural landscapes, and help to maintain and restore biodiversity. We developed a spatially explicit model to assess the relative importance of dispersal by wind and dispersal by water through drainage ditches for two wetland plant species in agricultural l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 64 publications
4
55
0
Order By: Relevance
“…In contrast to L. europaeus, O. aquatica was found almost exclusively in stagnant ditches, where wind may be the main driver of hydrochorous propagule dispersal. Several studies have shown that wind-driven hydrochory can be efficient, but with lower observed dispersal distances than observed in lotic systems (Soomers et al, 2010(Soomers et al, , 2013.…”
Section: Ditches As Dispersal Corridors For Hydrochorous Plant Speciementioning
confidence: 99%
“…In contrast to L. europaeus, O. aquatica was found almost exclusively in stagnant ditches, where wind may be the main driver of hydrochorous propagule dispersal. Several studies have shown that wind-driven hydrochory can be efficient, but with lower observed dispersal distances than observed in lotic systems (Soomers et al, 2010(Soomers et al, , 2013.…”
Section: Ditches As Dispersal Corridors For Hydrochorous Plant Speciementioning
confidence: 99%
“…The funders had no role in the design of the study; in the collection, analyses, or interpretation of data; in the writing of the manuscript, and in the decision to publish the results. Bird habitat Open water salt marsh management and mosquito ditches USA [191] Integrated marsh management USA [192] Rice fields Philippines [193], Brazil [189], China, Japan [194], France [195] [197,198] Wetland/aquatic plant habitat Paddies and ditches China [199,200] USA [191] Hot springs swimming pools and baths Turkey [211] …”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…In order to develop comprehensive IAS prevention and control measures, species risk assessments must consider not only broad invasion pathway categories, but also specific vectors (Essl et al, 2015). Currently, however, our understanding of the natural dispersal processes operating between hydrologically unconnected water bodies remains limited (Soomers et al, 2013;Incagnone et al, 2015;Coughlan et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%